Piloting a trachomatous trichiasis patient case-searching approach in two localities of Sudan. (20th April 2020) - Sanders, Angelia M; Adam, Maha; Aziz, Nabil; Callahan, E Kelly; Elshafie, Belgesa E
Abstract: Background: Approximately 1.9 million people have become blind or visually impaired from trachoma, the leading cause of infectious blindness. Trachoma prevalence surveys conducted in Sudan have shown that thousands of Sudanese suffer from the advanced stages of the disease, trachomatous trichiasis (TT), and warrant sight-saving surgery. Sudan's National Trachoma Control Program (NTCP) provides free TT surgery; however, given that many TT patients live in remote areas with limited access to health services, identifying patients and providing eye care services has proved challenging. For this reason, the Sudan NTCP piloted a systematic TT case-finding approach to identify patients. Methods: In Gedarif state, 11 villages in Baladyat el Gedarif locality and 21 villages in West Galabat locality were included in a TT case-searching activity from September to November 2018. TT case finders were selected from the villages where the activity took place and were trained by ophthalmic medical assistants to identify possible patients. Results: Of 66 626 villagers examined, 491 were identified as having TT by TT case finders. Of those, 369 were confirmed as true cases by the TT surgeons, a 75.2% (369/491) success rate. Conclusions: The TT case-finding approach provides an example of an effective method for identifying TT patients and should be expanded to other parts of the country known to be endemic for trachoma.